In Vitro And in Vivo Antidiabetic Activity of Ethanol Extract and Fractions of Hibiscus surattensis L Leaves - Yuliet Yuliet; Elin Yulinah Sukandar; I Ketut Adnyana (Indonesian Journal of Pharmaceutical Science and Technology, 2018)
Hisbiscus surattensis L the local name “tamoenju” is utilized by ethnic Sumari (Central Sulawesi) as an antidiabetic herbal, but de nitive studies on ef cacy and safety are lacking. Therefore, this study was aimed to investigate the antidiabetic activity of ethanolic extract of the leaves and fractions using in vitro and in vivo models. Ethanol extract (EE) of the leaves of H. surattensis L was prepared by maceration. The ethanol extract was separated into three fractions by liquid/liquid extractions to yield n-hexane (HF), ethyl acetate (EAF) and water fraction (WF). Firstly, the extract and fractions were tested for its inhibitory activity on α-glucosidase in vitro. The results showed IC50 EE, HF and WF more than 5000 ppm while the IC50 fraction of EAF 3888.34 ppm. Then, oral glucose tolerance test (OGTT) of the extract/fractions were carried out in normal mice. On OGTT, the ethanol extract, EAF, and WF at doses of 150 and 300 mg/kg BW were able to inhibit increasing the level of glucose in the blood. The results showed that the extract and fraction of H. surattensis L leaves in vitro had no effect as α-glucosidase inhibitor but in vivo had the hypoglycemic effect especially on the fraction of ethyl acetate and the water fraction. Key words: α-glucosidase, antidiabetic, Hibiscus suratttensis, glucose tolerance.